Use Wiki for Building an On-Line Collaborative Learning - Ann Zeki Ablahd (Tikrit Journal of Engineering Sciences, 2018)
It is important step to use a new technology for collaborative learning. The aim of this research is to facilitate collaborative learning group, increase a skill of learning, extending the knowledge of wiki in building online web collaborative learning activities system of computer science departments, by development a standards learning using free collaborative Wikispaces. The built system is called ComWiki. The ComWiki is an online collaborative system for learning. Includes delegation and Coordinate of responsibilities between group of members and share their opinions and ideas. The responsibilities such as exchange of views and important information, experiences of different professors with interaction between them. This work is published in http://ccomwiki.wikispaces.com. ComWiki is used mechanism for adding a trust more than others by enhancing online cooperative and collaborative education in using a non-open source Wikispaces application. ComWiki support a protection media for all information to prevent changing by web users and ease of use. ComWiki has a different media of learning like pictures, videos, text, chatting.